Orthodontic Treatment Combined with Surgical Intervention for Management of Impacted Maxillary Permanent Central Incisors: A Case Series - Kasturi Mukherjee; Poulomi Roy; Vikrant Omprakash Shetty; Prakash Banerjee; Shyamal Bar (Journal of Pharmacy and Bioallied Sciences)
Impacted maxillary central incisors prevalence is uncommon. This has a substantial impact on the patient’s self-esteem and aesthetic issues. A successful orthodontic resolution requires a combination of surgical exposure, bracket attachment, and extrusion. The surgical orthodontic method is the best option for treating impacted maxillary central incisors. In this case series, three patients with central incisor impaction reported missing teeth and unaesthetic appearance. All the cases were treated with surgical exposure, followed by orthodontic traction to restore smiling aesthetics.